The relationship between physical and psychological symptoms and health care utilization in hospitalized patients with advanced cancer. Issue 23 (23rd October 2017) - Nipp, Ryan D.; El‐Jawahri, Areej; Moran, Samantha M.; D'Arpino, Sara M.; Johnson, P. Connor; Lage, Daniel E.; Wong, Risa L.; Pirl, William F.; Traeger, Lara; Lennes, Inga T.; Cashavelly, Barbara J.; Jackson, Vicki A.; et al.
Abstract : BACKGROUND: Patients with advanced cancer often experience frequent and prolonged hospitalizations; however, the factors associated with greater health care utilization have not been described. We sought to investigate the relation between patients' physical and psychological symptom burden and health care utilization. METHODS: We enrolled patients with advanced cancer and unplanned hospitalizations from September 2014‐May 2016. Upon admission, we assessed physical (Edmonton Symptom Assessment System [ESAS]) and psychological symptoms (Patient Health Questionnaire 4 [PHQ‐4]). We examined the relationship between symptom burden and healthcare utilization using linear regression for hospital length of stay (LOS) and Cox regression for time to first unplanned readmission within 90 days. We adjusted all models for age, sex, marital status, comorbidity, education, time since advanced cancer diagnosis, and cancer type. RESULTS: We enrolled 1, 036 of 1, 152 (89.9%) consecutive patients approached. Over one‐half reported moderate/severe fatigue, poor well being, drowsiness, pain, and lack of appetite. PHQ‐4 scores indicated that 28.8% and 28.0% of patients had depression and anxiety symptoms, respectively. The mean hospital LOS was 6.3 days, and the 90‐day readmission rate was 43.1%. Physical symptoms (ESAS: unstandardized coefficient [B], 0.06; P < .001), psychological distress (PHQ‐4 total: B, 0.11; P = .040), and depression symptoms (PHQ‐4 depression: B, 0.22; P = .017) were associated with longer hospital LOS. Physical (ESAS: hazard ratio, 1.01; P < .001), and anxiety symptoms (PHQ‐4 anxiety: hazard ratio, 1.06; P = .045) were associated with a higher likelihood for readmission. CONCLUSIONS: Hospitalized patients with advanced cancer experience a high symptom burden, which is significantly associated with prolonged hospitalizations and readmissions. Interventions are needed to address the symptom burden of this population to improve health care delivery and utilization. Cancer 2017;123:4720‐4727 . © 2017 American Cancer Society . Abstract : Hospitalized patients with advanced cancer in this study experience a high symptom burden, with >50% reporting moderate‐to‐severe fatigue, pain, drowsiness, and poor appetite. Patients' physical and psychological symptoms are associated with longer hospital length of stay and greater risk for unplanned hospital readmissions.